Impact of Economic Growth, Energy Consumption and Urban Population to Climate Change in Indonesia Period 1985-2019 - Annisa; Adawiyah, Robi'atul; Heppi, Dri; Bashir, Abdul (AFEBI Economic and Finance Review, 2022)
Economic growth, energy consumption and urban population have positive and significant impact to climate change. The condition of economic growth, energy consumption and urban population in Indonesia during the period 1985-2019 continued to increase and that also will increase the CO2 emission and will make the heat trapped on earth and increasing earth temperature and it made the climate change. In addition, energy consumption is one indicator by which the level of technology can be measured, in which the widespread use of environmentally friendly technology can reduce energy consumption of fossil fuels. However, it can also lead to an increase in energy consumption through increased levels of efficiency, increased income and human nature which tends to be wasteful and ineffective